2006
DOI: 10.1084/jem.20052242
|View full text |Cite
|
Sign up to set email alerts
|

Block of C/EBPα function by phosphorylation in acute myeloid leukemia with FLT3 activating mutations

Abstract: Mutations constitutively activating FLT3 kinase are detected in ∼30% of acute myelogenous leukemia (AML) patients and affect downstream pathways such as extracellular signal–regulated kinase (ERK)1/2. We found that activation of FLT3 in human AML inhibits CCAAT/enhancer binding protein α (C/EBPα) function by ERK1/2-mediated phosphorylation, which may explain the differentiation block of leukemic blasts. In MV4;11 cells, pharmacological inhibition of either FLT3 or MEK1 leads to granulocytic differentiation. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
185
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(194 citation statements)
references
References 65 publications
9
185
0
Order By: Relevance
“…11,18 On the other hand, it has been shown that FLT3 ITD can phosphorylate C/EBPa, which could lead to a loss of function in the absence of other mutations explaining why some AML only carry a monoallelic C/EBPa mutation. 21,22 In addition, recent work using retroviral overexpression demonstrated that a C-terminal Cebpa mutation (C/EBPa-C m ) was sufficient to cause AML and that FLT3 ITD could shorten the latency of AML induced by C/EBPa-C m . 23 To elucidate this discrepancy, we also monitored hematopoietic chimeras with single, either N-terminal (L allele) or C-terminal…”
Section: Resultsmentioning
confidence: 99%
“…11,18 On the other hand, it has been shown that FLT3 ITD can phosphorylate C/EBPa, which could lead to a loss of function in the absence of other mutations explaining why some AML only carry a monoallelic C/EBPa mutation. 21,22 In addition, recent work using retroviral overexpression demonstrated that a C-terminal Cebpa mutation (C/EBPa-C m ) was sufficient to cause AML and that FLT3 ITD could shorten the latency of AML induced by C/EBPa-C m . 23 To elucidate this discrepancy, we also monitored hematopoietic chimeras with single, either N-terminal (L allele) or C-terminal…”
Section: Resultsmentioning
confidence: 99%
“…108 Recent reports have demonstrated that MEK/MAPK inhibition can release cells from FLT3-ITD-mediated differentiation blockade. 109 These findings suggest that MEK is a rational target for combination studies with available FLT3 inhibitors.…”
Section: Flt3 Monoclonal Anitbodiesmentioning
confidence: 98%
“…Leukemias involving the internal tandem duplication (ITD) in FLT-3 (Fms-like tyrosine kinase 3) that constitutively activates FLT-3 kinase activity have been reported to block C/EBPα function via phosphorylation at Serine 21 (S21) in the C/EBPα protein. Hence, the increased FLT-3 activity appears to both increase cellular proliferation and increase cell viability and also prevent C/EBPα from inducing granulocytic differentiation [18]. Decreased expression of C/EBPα has also been described in AML with the t(8;21) translocation resulting in the AML1-ETO fusion protein.…”
Section: Ccaat Enhancer Binding Protein Alpha (C/ebpα)mentioning
confidence: 98%
“…In leukemias harboring the FLT-3-ITD mutation, constitutive FLT-3 kinase activity results in sustained phosphorylation at S21 in the C/EBPα protein. Phosphorylation at S21 in turn has been shown to interfere with the ability of C/EBPα to induce granulocytic differentiation, an observation that may explain the differentiation block associated with leukemia [18].…”
Section: Ccaat Enhancer Binding Protein Alpha (C/ebpα)mentioning
confidence: 99%